2022
DOI: 10.1039/d1se02034j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped porous carbon nanosheets as a robust catalyst for tunable CO2 electroreduction to syngas

Abstract: High-efficiency electrochemical CO2-to-syngas conversion with tunable H2/CO ratio is a desirable strategy to achieve energy storage and subsequent carbon neutral. However, the customization of H2/CO ratio is still a major...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Hence, heteroatoms doping is an interesting strategy for the CO2ER. Even though most studies deal with N-doping [13][14][15][16][17][25][26][27][28], recent studies have shown the benefits of doping and dual codoping with other elements (e.g., O- [19], B- [24], S- [21], P- [39]). Further research should be drawn in this direction.…”
Section: Nanoconfinement and Surface Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, heteroatoms doping is an interesting strategy for the CO2ER. Even though most studies deal with N-doping [13][14][15][16][17][25][26][27][28], recent studies have shown the benefits of doping and dual codoping with other elements (e.g., O- [19], B- [24], S- [21], P- [39]). Further research should be drawn in this direction.…”
Section: Nanoconfinement and Surface Functionalizationmentioning
confidence: 99%
“…The latter is an essential prerequisite step for the electrochemical reduction of CO 2 , although often overlooked. Although not much explored for the CO2ER, most efforts have focused in introducing modifications to tailor the electrocatalytic centers of the carbon materials via doping [13][14][15][16][17][18] or nanopore control [19][20][21][22]. The improved performance (described in terms of conversion, faradaic efficiency, selectivity) has been mainly attributed to the effect of heteroatom doping on the electronic properties of the carbon material, and/or creating specific electrocatalytic active sites [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig.5Recently reported H 2 /CO ratios of various catalysts used for syngas production at different applied potentials. (a) Heteroatom-doped carbon catalysts (N-CNTs,42 BPNC,14 NCSP-70,51 UNCNs-900,52 NCN-6,53 and NBC54 ), (b) metal catalysts (OD-Cu NA,55 ZnOCNT,56 I-Ag,57 AuCu 2 /CNT,58 Au Θ Cu ∼ 3/3,59 and Co rate-aligened60 ), (c) M-N-C single-atom catalysts (Ni-hG,23 CoNi-NC,24 Co-N-C-Ph,61 Fe-N-C,33 P/Ni-4@Ni-NC,62 and Co@CoNC-90063 ) and (d) Ni-N co-doped ultrathin carbon nanosheet electrodes. The shaded regions are the areas with the optimal syngas ratios.…”
mentioning
confidence: 99%